Investigating terrestrial water storage changes in Southwest China by integrating GNSS and GRACE/GRACE-FO observations - Xinghai Yang; Linguo Yuan; Zhongshan Jiang; Miao Tang; Xianjie Feng; Changhai Li (Journal of Hydrology: Regional Studies, 2023)
Study region: Southwest China. Study focus: Terrestrial water storage (TWS) changes estimated from the Global Navigation Satellite System (GNSS) and Gravity Recovery and Climate Experiment missions (GRACE/GRACE-FO) are critical data sets for hydrological studies. To obtain a broader and unified spatiotemporal scale than a single method, we designed two improved joint inversion methods (JIMs). The joint inversion method 1 and 2 (JIM1 and JIM2) are based on GRACE/GRACE-FO-derived virtual stations and 3-degree mascons from Jet Propulsion Laboratory, respectively. We focused on investigating TWS changes in Southwest China using JIM1 and JIM2 New hydrological insight for the region: The synthetic test showed that JIM1 and JIM2 had lower root-mean-square-errors than a GNSS-Only inversion method (GNSS-IM), with reductions of 22% and 37%, respectively, confirming their feasibility. The results of JIMs using actual GNSS and GRACE/GRACE-FO data showed that the area-averaged JIMs-TWS estimates were consistent with GRACE/GRACE-FO-TWS and GNSS-IM-TWS, but JIM2-TWS was overfit to GNSS-IM-TWS. Then, we utilized JIM1-TWS to investigate hydro-climate relationships and quantify drought events. The results revealed a strong agreement between JIM1-dTWS/dt and precipitation-evapotranspiration-runoff with a correlation coefficient of 0.89. Precipitation contributed the most to TWS changes. Furthermore, three hydrological drought events were detected, with the third event being the most severe, lasting for 20 months, resulting in a total TWS loss of − 501 km3, and being categorized as an exceptional drought.